The Application of Artificial Intelligence (AI) in Determining Student Boarding House Around the UIN Bukittinggi Campus - AZIL, Azil; Liza Efriyanti; Sarwo Derta; Firdaus Annas (BiCED Proceeding, 2024)
UIN Bukittinggi students who come from various regions are in need of a strategic and comfortable place to live. Students often have difficulty finding the right choice during the conventional boarding house search process. In this study, artificial intelligence (AI)-based confidence factor (CF) will be used to help students choose the right boarding place. The methods used include data collection of student preferences and CF analysis to make suggestions based on price, distance, and facilities. The results show that Kos Putri Bunda and Kos Putra Sukses have the highest CF values. This shows that these two boarding houses are very much in line with students' preferences. The discussion shows how this system helps students make decisions and improve the search for boarding houses. The discovery of this research is the application of the CF method in particular .